Quantifying dose uncertainties resulting from cardiorespiratory motion in intensity-modulated proton therapy for cardiac stereotactic body radiotherapy - Wei, Weige; Li, Zhibin; Xiao, Qing; Wang, Guangyu; He, Haiping; Luo, Dashuang; Chen, Li; Li, Jing; Zhang, Xiangyu; Qin, Taolin; Song, Ying; Li, Guangjun; et al. (Frontiers in Oncology, 2024)
Background: Cardiac stereotactic body radiotherapy (CSBRT) with photons efficaciously and safely treats cardiovascular arrhythmias. Proton therapy, with its unique physical and radiobiological properties, can offer advantages over traditional photon-based therapies in certain clinical scenarios, particularly pediatric tumors and those anatomically challenging tumors. However, dose uncertainties induced by cardiorespiratory motion are unknown. Objective: This study investigated the effect of cardiorespiratory motion on intensity-modulated proton therapy (IMPT) and the effectiveness of motion-encompassing methods. Methods: We retrospectively included 12 patients with refractory arrhythmia who underwent CSBRT with four-dimensional computed tomography (4DCT) and 4D cardiac CT (4DcCT). Proton plans were simulated using an IBA accelerator on the 4D average CT. The prescription was 25 Gy in a single fraction, with all plans normalized to ensure that 95% of the target volume received the prescribed dose. 4D dose reconstruction was performed to generate 4D accumulated and dynamic doses. Furthermore, dose uncertainties due to the interplay effect of the substrate target and organs at risk (OARs) were assessed. The differences between internal organs at risk volume (IRV) and OAR real (manually contoured on average CT) were compared. In 4D dynamic dose, meeting prescription requirements entails V25 and D95 reaching 95% and 25Gy, respectively. Results: The 4D dynamic dose significantly differed from the 3D static dose. The mean V25 and D95 were 89.23% and 24.69Gy, respectively, in 4DCT and 94.35% and 24.99Gy, respectively, in 4DcCT. Eleven patients in 4DCT and six in 4DcCT failed to meet the prescription requirements. Critical organs showed varying dose increases. All metrics, except for Dmean and D50 , significantly changed in 4DCT; in 4DcCT, only D 50 remained unchanged with regards to the target dose uncertainties induced by the interplay effect. The interplay effect was only significant for the D max values of several OARs. Generally, respiratory motion caused a more pronounced interplay effect than cardiac pulsation. Neither IRV nor OAR real effectively evaluated the dose discrepancies of the OARs. Conclusions: Cardiorespiratory motion can introduce dose uncertainties during IMPT. Motion-encompassing techniques cannot entirely compensate for the dose discrepancies. Individualized 4D dose assessments are recommended to verify the effectiveness and safety of CSBRT.